The impact of the density of individual social networks on WeChat usage in intimate relationships among Chinese youngsters - Nie, Zhou; Li, Mingzhu; Waheed, Moniza; Kasimon, Diyana; Wan Abas, Wan Anita (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
WeChat has become the most popular type of social media among youngsters in China. They use it for various reasons including communicating in intimate relationships. This study aims to investigate the impact of the density of individuals’ social networks on WeChat Usage in Intimate Relationships among Chinese youngsters, guided by the Theory of Planned Behaviour (TPB). An online questionnaire was constructed and disseminated to respondents online. In total, 923 undergraduate students from Chinese universities completed the questionnaires. Utilizing Structural Equation Modelling, findings show that the density of individuals’ social networks has a limited impact on WeChat usage. On the other hand, TPB factors such as subjective norms and perceived control bring a substantial impact on WeChat usage, while attitude has a less significant impact. These results indicate that Chinese youngsters exhibit strong attributes of the collective culture. This study also suggests that future social media research should place more emphasis on cultural and social factors.